Răspuns :
[(2^3)^4: (2^2)^5 + (3^3)^9 : 3^24 + 2^12 : 2^11)] : 3 =
[ 2^12 : 2^10 + 3^27 : 3^24 + 2] : 3 =
[ 2^2 + 3^3 + 2] : 3 =
[ 4 + 27 + 2] : 3
33 : 3 =
11
[ 2^12 : 2^10 + 3^27 : 3^24 + 2] : 3 =
[ 2^2 + 3^3 + 2] : 3 =
[ 4 + 27 + 2] : 3
33 : 3 =
11
(8^4 : 4^5 + 27^9 : 3^24 + 2^12 : 2^11) : 3 =
= [(2^3)^4:(2^2)^5+(3^3)^9:3^24+2^1] :3 =
= (2^12 : 2^10 + 3^27 : 3^24 + 2) : 3 =
= (2^2 + 3^3 + 2) : 3 =
= (4 + 27 + 2) : 3 =
= 33 : 3 =
= 11
= [(2^3)^4:(2^2)^5+(3^3)^9:3^24+2^1] :3 =
= (2^12 : 2^10 + 3^27 : 3^24 + 2) : 3 =
= (2^2 + 3^3 + 2) : 3 =
= (4 + 27 + 2) : 3 =
= 33 : 3 =
= 11